PENGARUH PEMBELAJARAN BIOLOGI BERBASIS STEAM TERINTEGRASI LITERASI SAINS TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Hilman Hadi; Nur'aini; Wawan Muliawan; Marhamah (UNIVERSITAS HAMZANWADI, 2024)
This study aims to determine the effect of STEAM-based biology learning integrated with science literacy on students' creative thinking skills. This type of research uses quasi-experimental design. The population of this study were all grade X students at MA Mu